2017
DOI: 10.1007/s11284-017-1510-z
|View full text |Cite
|
Sign up to set email alerts
|

Basin‐wide impacts of climate change on ecosystem services in the Lower Mekong Basin

Abstract: Water resources support more than 60 million people in the Lower Mekong Basin (LMB) and are important for food security-especially rice production-and economic security. This study aims to quantify water yield under near- and long-term climate scenarios and assess the potential impacts on rice cultivation. The InVEST model (Integrated Valuation of Ecosystem Services and Tradeoffs) forecasted water yield, and land evaluation was used to delineate suitability classes. Pattern-downscaled climate data were special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 32 publications
1
31
1
2
Order By: Relevance
“…In our study, we highlighted similarly good performances from HadGEM2-ES, CCSM4, and IPSL-CM5A-MR over the LMB, which is part of the Asian monsoon region, and part of the Mekong River Basin, which are both affected by the southwest monsoon. However, our results showed differences from the above studies, which indicated that it is significant to assess GCM performance not only at a large scale, but also at a regional scale: A river basin such as the LMB should especially be taken into important consideration due to its special geographical position and climatic characteristics, as well as its significant effects [30,31].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In our study, we highlighted similarly good performances from HadGEM2-ES, CCSM4, and IPSL-CM5A-MR over the LMB, which is part of the Asian monsoon region, and part of the Mekong River Basin, which are both affected by the southwest monsoon. However, our results showed differences from the above studies, which indicated that it is significant to assess GCM performance not only at a large scale, but also at a regional scale: A river basin such as the LMB should especially be taken into important consideration due to its special geographical position and climatic characteristics, as well as its significant effects [30,31].…”
Section: Discussioncontrasting
confidence: 80%
“…Moreover, further increases in population and accelerated urbanization have exacerbated the demand for water resources [29]. Additionally, changes in precipitation are likely to have great impacts on the water cycle system, water resources, and agricultural production of the Lower Mekong Basin (LMB) [5,30,31]. Therefore, assessing GCM performances in simulating precipitation is essential for future precipitation change and policy-making over the LMB.…”
Section: Introductionmentioning
confidence: 99%
“…Future climate change will affect water yield and rice cultivation in the tributary countries over the Lower Mekong Basin (LMB) [30]. Due to the population growth in the Lower Mekong Basin (LMB), the demands for agricultural products from the LMB is expected to increase by 20-50% in the next 30 years [31].…”
Section: Introductionmentioning
confidence: 99%
“…A further four original articles include studies of the status of biodiversity, ecosystem structure, and ecosystem services in terrestrial, riverine, and marine environments in different parts of Asia. In their study, Trisurat et al (2018) present a forecast of future changes in ecosystem services in the Lower Mekong Basin by quantifying changes in water yield, while Nguyen et al (2018) review plans to conserve the wetlands in the Vietnamese Mekong Delta by changing the present hydrological management. Galindon et al (2018) compare the status of biodiversity in forests in limestone quarries in different sub-regions of the Philippines with different management histories (reforestation).…”
Section: Editorialmentioning
confidence: 99%